Prevalence of Sexually Transmitted Infections (Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis and Human Papillomavirus) in Female Attendees of a Sexually Transmitted Diseases Clinic in Ulaanbaatar, Mongolia - Suzanne M. Garland; Sepehr N. Tabrizi; Shujun Chen; Chultemsuren Byambaa; Khalzan Davaajav (Hindawi Limited, 2001)
Background: Epidemiological data suggest that the prevalence of syphilis, gonorrhea and trichomoniasis has increased in both urban and rural areas of Mongolia. These data are primarily substantiated by notifications of cases of clinically apparent disease in both rural and urban areas, plus laboratory diagnoses from the AIDS/STD Reference Center,Ulaanbaatar. In the past 5 years, however, there has been a marked decline in the total number of patients being screened for sexually transmitted infections (STIs). An assessment of true prevalence of STIs in a female population attending an urban sexually transmitted diseases (STD) clinic was therefore commenced.